Nice try, tooth fairy - Olson, Mary W.; Tillotson, Katherine (New York : Scholastic, 2000)
Hoping to get back her lost tooth, Emma writes a series of letters to the Tooth Fairy, but when the wrong teeth keep getting returned the mistakes create complications.
Keywords: Children's stories